Regulasi Emosi dan Harga Diri sebagai Faktor Psikologis Penentu Ketahanan Ibu dalam Pemberian Air Susu Ibu Eksklusif pada Ibu Tidak Bekerja - Hotimah, Hananik; Fajar, Nur Alam; Sunarsih, Elvi (FORIKES, 2025)
Breast milk is the best source of nutrition for babies, especially during the first six months of life. One important aspect of successful breastfeeding that is often overlooked is the mother's psychological well-being, especially emotional regulation and self-esteem. The purpose of this study was to obtain information on emotional regulation and self-esteem as psychological factors that influence maternal resilience in exclusive breastfeeding in non-working mothers. This study was a narrative literature review from four databases, namely BMC Pregnancy and Childbirth, BMC Public Health, Google Scholar and Google Scholar Indonesia until November 6, 2025. The keywords used for the BMC database were